2017
DOI: 10.1097/igc.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Survival Outcomes in Advanced Serous Ovarian Cancer Patients Treated With Primary Debulking Surgery Versus Neoadjuvant Chemotherapy

Abstract: Our findings suggest that among women with no residual disease, survival is better among those who undergo primary debulking surgery than treatment with neoadjuvant chemotherapy. The latter should be reserved for women who are deemed not to be candidates for primary debulking surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 29 publications
4
39
0
2
Order By: Relevance
“…To address these matters and determine the ideal treatment strategy, the ongoing Trust trial, enrolling centers guaranteeing high surgical quality and having as its primary endpoint overall survival (OS), randomized 1:1 UDS versus NACT‐IDS, patients with FIGO‐stage IIIB‐IVB tubo‐ovarian and peritoneal carcinoma. Even though surgical quality needs to be more highly standardized, studies comparing UDS versus NACT tend to overlook the need to analyze data for a specific tumor histotype or, quantify precisely the peritoneal tumor burden and evaluate in detail responses to NACT . Equally important, detailed information on the clinical history of the disease, the timing, site, treatment of recurrence, and its results could help in understanding treatment outcome in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…To address these matters and determine the ideal treatment strategy, the ongoing Trust trial, enrolling centers guaranteeing high surgical quality and having as its primary endpoint overall survival (OS), randomized 1:1 UDS versus NACT‐IDS, patients with FIGO‐stage IIIB‐IVB tubo‐ovarian and peritoneal carcinoma. Even though surgical quality needs to be more highly standardized, studies comparing UDS versus NACT tend to overlook the need to analyze data for a specific tumor histotype or, quantify precisely the peritoneal tumor burden and evaluate in detail responses to NACT . Equally important, detailed information on the clinical history of the disease, the timing, site, treatment of recurrence, and its results could help in understanding treatment outcome in individual patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent comparative study of two groups, May et al (16) reported that 5-year survival was better for patients undergoing PDS than in patients who received NAC (39% vs 27%; p=0.02). However, the gross residual tm (>1 cm) ratio in the PDS group was higher in their study (28% vs 19%, p=0.02).…”
Section: Discussionmentioning
confidence: 99%
“…También hubo una tendencia no significativa a mayor SG en las pacientes tratadas con CCR de entrada (SG a 5 años del 89 vs. 44%; p = 0.097). Por tanto, en nuestro estudio, al igual que en otros estudios publicados hasta la fecha, la CCR de entrada se asoció con mejor pronóstico en comparación con la CCR de intervalo tras quimioterapia neoadyuvante 17,18 .…”
Section: Discussionunclassified